Problem miejskiego centrum w obliczu dynamicznych przemian urbanistycznych i kulturowych — na przykładzie Bielska-Białej - Błahut, Grzegorz (Studia Etnologiczne i Antropologiczne, 2010)
The phenomenon of the centre, covering a series of conceptions concerning given wholes on the scale of both a micro and macro‑cosmos is also visible in the architecture. The architecture, on the other hand, concerning a house or a temple or their concentrated multitude in the form of the city, reflects given mythic structures. In Middle‑aged cities surrounded by the walls, the localization of the centre was not a problem at all. Nowadays, the centre of a big, modern city may be not only difficult to locate, but also, as Aleksander Wallis points out, difficult to define. He tries to take the criterion of function, as a result of which several overlapping city centres, such as historical, trade, administrative ones can appear in the area of the city. In the process of city development one can observe a dynamics of the urban centres, dependent on economic, urbanist and cultural changes. An interesting example of this phenomenon is a double city Bielsko‑Biała, where in the area of the same city — Bielsko — a new centre appeared and the oldest centre was located in the place of the old market square in the last few years. Both centres constitute a cultural area. The difference between them lies in the fact that they refer to different value systems. What seems interesting is the fact the new centre of a trade, service, and recreational nature borrows the cultural functions associated with other places and institutions in the city, such as the theatre, the house of music, galleries. Undoubtedly, it distorts a cultural ecosystem of the urban space, especially in reference to a widely‑understood centre. A relationship of these two centres is defined by the state of rivalry and contradiction, but there are also such areas that complete each other. The attempt to unify the centre and establish its location is visible above all in symbolic forms and forms of realization of given functions. An existing divergence can be eradicated by the users of these spaces not only mentally, but also the architects and urbanists thanks to a further development of the new centre in a direction of the Old Town in Bielsko, which is indicated by the already defined projects. There exist the differences between generations in the perception of the centre, as well as between the inhabitants of Bielsko‑Biała and people commuting and coming from other places. As it was in reference to the Ancient and Middle‑aged cities, the acquaintance of the centre of the contemporary city is important in a description of many present‑day social and cultural phenomena.